The chain-mediating role of perceived stress and problematic smartphone use in the link between critical thinking and academic engagement among Spanish adolescents - Arrivillaga, Christiane; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (MUNI, 2022)
Because problematic smartphone use (PSU) is rising among adolescents, it is vital to analyze the potential causes and psychosocial consequences affecting this target population. Current theoretical frameworks suggest that specific personal core characteristics might predispose individuals to experience increases in this problematic behavior over time. Additionally, PSU has been conceptualized as a maladaptive coping mechanism to manage negative emotions. The present study aimed at analyzing a personal resource, critical thinking disposition, and a potential negative consequence, reduced academic engagement, and the underlying role of perceived stress and PSU in this association among Spanish adolescents. The sample consisted of 688 adolescents (54% females, 46% males) aged 12 to 18 years from Southern Spain. Participants completed self-report questionnaires to assess critical thinking disposition (VIA-Youth), perceived stress (Perceived Stress Scale), PSU (Smartphone Addiction Scale- Short Version), and academic engagement (Utrecht Work Engagement Scale-Students). We analyzed a serial mediation model using PROCESS (SPSS), in which critical thinking disposition was the independent variable, perceived stress and PSU were the first and second mediators, respectively, and academic engagement was the outcome variable. Our results indicated that lower critical thinking disposition was linked to increased perceived stress, which was associated with higher PSU, resulting in decreased academic engagement. These findings provide empirical support for the pathways model of PSU, the maladaptive coping theories, and the I-PACE model of behavioral addictions. Furthermore, we discuss our results highlighting the important implication of training adolescents to think critically regarding their smartphone usage to reduce their stress levels, to avoid using smartphones as a coping strategy, and hence, to improve their student's attitudes toward school.
Keywords: Teléfonos móviles y jóvenes; Tecnología - Aspectos sociológicos; Rendimiento académico; Adolescentes - Trastornos de la conducta; Critical thinking; Stress; Problematic smartphone use; Academic engagement; Adolescents; Serial mediation